1966
DOI: 10.1111/j.1439-0396.1966.tb00087.x
|View full text |Cite
|
Sign up to set email alerts
|

The Principles of Ensilage

Abstract: Zusammenfassung Dieses übersichtsreferat bringt Ergebnisse einer Arbeitsgruppe aus Edinburgh, die in den letzten 15 Jahren den Silierungsprozeß untersucht hat. Die Grundlagen der Silie‐rung werden besprochen, und Angaben werden gemacht über Ausrüstung, chemische Methoden und bakteriologische Verfahren. Beschrieben werden Einflüsse soldier Fak‐toren, wie Feuchtigkeit und Temperatur einerseits, chemischer Zusammensetzung, physikalischer Beschaffenheit und Mikroflora des Ausgangsmaterials andererseits, auf den Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
3
9
0
Order By: Relevance
“…The production of biogenic amines in silage is determined by the extent of proteolysis and/or the rate of decarboxylation [16]. In this study, the correlation between amine content and proteolysis was confirmed with respect to the degree of wilting, ploidy and the effect of diploid cultivars.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The production of biogenic amines in silage is determined by the extent of proteolysis and/or the rate of decarboxylation [16]. In this study, the correlation between amine content and proteolysis was confirmed with respect to the degree of wilting, ploidy and the effect of diploid cultivars.…”
Section: Discussionsupporting
confidence: 53%
“…Parada and Krynia had no limiting effect on the rate of fermentation (no significant effect on the concentrations of lactic acid, acetic acid, ethanol and WSC). A lower decrease in organic matter content during the ensilage of diploid red clover (a lower ash content of silage, compared with green forage), at similar lactic acid concentrations, could be indicative of more efficient lactic acid fermentation (greater contribution of homofermentative microflora) [16]. The genetic forms of red clover and cultivars within these forms had the strongest effect on butyric acid concentrations in silage.…”
Section: Discussionmentioning
confidence: 99%
“…The production of effluent in silages can be related to the level of DM of the plant, the cell wall rupture and bulk density (Alli et al, 1985), as well as to the formation of water during the fermentation of glycose into ethanol and the decrease of DM content due to losses (McDonald et al, 1991). In this paper, the silos sealed with plastic sheet showed the highest production of effluents, although the levels of DM and the fermentative losses were very similar to silos sealed with lids.…”
Section: Resultsmentioning
confidence: 77%
“…Ávila et al (2010) isolated nine distinct species of yeast from samples of five sugarcane silages and observed that most of them assimilated lactate and all species grew well in a pH lower than 3.3. The RB72-454 variety, the same used in this study was noticed by the authors as with higher occurrence of Torulaspora debrueckii and Pichia anomala, which, under conditions of anaerobiosis, obtain energy from the fermentation of sugars, producing 2 moles of CO 2 and two molecules of water for each mol of glycose that is fermented into ethanol (McDonald et al, 1991).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation